High dietary protein, n − 3/n − 6 ratio and β‐carotene enhances Paracentrotus lividus (Lamarck, 1816) larval development. (6th August 2022) - Gomes, Ana S.; Lourenço, Sílvia; Santos, Pedro M.; Neves, Marta; Adão, Pedro; Tecelão, Carla; Pombo, Ana
Abstract: The nutritional characteristics of microalgae affect the growth, survival and fatty acid composition of sea urchin larvae. This study aimed to evaluate the influence of nutritive characteristics of single microalgal diets in Paracentrotus lividus (Lamarck, 1816) larval development, growth, and condition. Larvae of P. lividus were fed with three monospecific microalgal diets, Rhodomonas sp. (Rho), Dunaliella tertiolecta (Duna) and the diatom Chaetoceros calcitrans (Chae), and their development and growth were analysed until competence. Additionally, the fatty acid (FA) profile of larvae was analysed at competence and compared with the FA profile of the correspondent diet. The three groups of larvae attained competence simultaneously with differences in growth performance. The larvae fed with Chae attained the largest stomach and the shortest post‐oral arm. The larvae were able to accumulate long‐chain polyunsaturated fatty acids (PUFA), such as docosahexaenoic (DHA, C22:6 n − 3), eicosapentaenoic (EPA, C20:5 n − 3) and arachidonic (ARA, C20:4 n − 6) acids, either by assimilation and retention of dietary FA or by the synthesis from α‐linolenic acid (ALA, C18:3 n − 3) and linoleic acid (LA, C18:2 n − 6). Furthermore, the low DHA/EPA ratio and high EPA/ARA and n − 3/ n − 6 ratios of Rho and Chae and the high levels of the β‐carotene present in Chae improved larval growth and development. In conclusion, the results indicated that of the three microalgal diets tested, C. calcitrans provided important nutritional characteristics, especially in terms of FA composition and carotenoids, improving P. lividus larval growth and condition.